Visible-light driven generation of reactive radicals over BiFeO3/TiO2 nanotube array: experimental evidence and energetic mechanism - Zhao, Q.; Li, Xin Yong; Liu, Y.; Zhu, A. (Kluwer Academic Publishers, 2015)
© 2015, Springer Science+Business Media Dordrecht. BiFeO3-based materials have attracted broad interests due to their multiferric and photoactive properties, but there remains some controversial uncertainty about the electronic structures of various nanoparticles of BiFeO3. In this work, BiFeO3 nanoparticles smaller than 100 nm have grown into TiO2 nanotube array by an ultrasonic-immersion method. Some evidences on the energy band position of BiFeO3 nanoparticles in BiFeO3/TiO2 nanotube array were from the visible-light driven photo responses. Positive surface photovoltage polarity of the composite is the same as that of the pure TiO2 nanotube array, which reveals the photo-induced electron transfer from BiFeO3 nanoparticles to TiO2 nanotubes. Furthermore, both ·OH and ·O2 − radicals could be detected by the electron paramagnetic resonance (EPR) spin-trapping method. According to the EPR result, the valence band edge of BiFeO3 nanoparticles could be deduced as more positive than the potential at which ·OH radical could be generated. A scheme on the energy band alignment and photo-induced charges transfer processes is then proposed based on the observed visible-light photo activity of BiFeO3/TiO2 nanotube array.